PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS HOTS BERBANTUAN WEBSITE WORDWALL PADA MATERI BANGUN RUANG - Adnin Rizki Kasdina; Fitri Siti Sundari; Rukmini Handayani (STKIP Subang, 2023)
This study to khow how to develop HOTS-based assessment instruments assisted by wordwall websites on building material for classrooms V SDN Bantarkemang 2, as well as knowing the feasibility of assessment instruments using wordwall websites in the learning process. The method used in this study is using the ADDIE method (Analyze, Design, Development, Implementation, and Evaluation). This research begins with collecting information on the needs and problems that exist in elementary schools, designing assessment instruments, validating products to experts, revising products, and after that testing assessment instruments for students. The results of the feasibility trial of assessment instruments using the wordwall website show that this product is very feasible for use in learning. This is evidenced by the results of the response questionnaire of validators, evaluation experts, material experts, media experts and linguists by obtaining an average percentage of 98%, as well as student response questionnaires which obtained an average percentage of 99.7%. This is also supported by analyzing the validity of the question items, the reliability of the question items, the level of difficulty of the question items and the distinguishing power of the question items. So it can be concluded that the HOTS-based assessment instrument assisted by the wordwall website on classroom V building material is suitable for use by students.